Modifiable facilitators and barriers to exercise adherence in older adults with MCI/dementia using the Theoretical Domains Framework: a systematic review protocol - Jie Wang; Lina Wang; Xueting Zhen; Hang Yan; Hong Tao; Yaxiu Cai; Haiqin Chen; Chenxi Ge (BMJ Open)
Introduction Exercise has multiple benefits on maintaining or improving cognitive function for people with mild cognitive impairment (MCI)/dementia. However, many older adults with MCI/dementia are not sufficiently active to achieve these benefits. Allowing for the current studies on exercise adherence in older adults with MCI/dementia still have some deficiencies. This paper aims: (1) to identify the modifiable facilitators and barriers to exercise adherence for older adults with MCI/dementia in terms of the perspectives of patients, caregivers and healthcare professionals; (2) to organise the identified factors of exercise adherence based on the Theoretical Domains Framework (TDF) among included studies.Methods and analysis A systematic computerised literature search will be performed in the following online databases: PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure and Wan Fang Database, which published between January 1990 and June 2020. We will identify peer-reviewed publications which examined facilitators and barriers to exercise adherence. Searches will have no limitation in language publications using search terms related to exercise interventions, adherence and MCI/dementia. Two independent reviewers will screen titles, abstracts and full-text articles according to the predetermined inclusion and exclusion criteria. We will use the statistical software Nvivo V.12 to manage the information. Basing on the TDF, we will map identified modifiable facilitators and barriers of literature to the domains of TDF.Ethics and dissemination This review will summarise modifiable facilitators and barriers to exercise adherence for older adults with MCI/dementia for the first time. Ethical approval is not required as no primary data are collected. We are going to disseminate our findings to the scientific and medical community in peer-reviewed journals. The review findings will facilitate adequate and accurate access to care and treatment to help older adults with MCI/dementia have a broader adoption to exercise.PROSPERO registration number CRD42019117725.